Prevalence of asthmatic respiratory complications among the rural community of Tangail area in Bangladesh - Hossain, Md. Imam; Parvez, Masum; Zohora, Fatama Tous; Islam, Md. Shariful; Bari, Luthfunnesa (International Journal Of Community Medicine And Public Health, 2018)
Background: Asthmatic respiratory complications appear to be a notable public health consequence and associated with mortality, morbidity and economic burden worldwide. Globally several epidemiological studies have been conducted to assess the prevalence of asthmatic respiratory complications. As far our knowledge very few population based study have been conducted in Bangladesh to assess the magnitude of asthmatic respiratory complications focusing the rural community. Therefore the study was undertaken to assess the prevalence of asthma and related respiratory complications in the rural community of Tangail area in Bangladesh. Methods: This human population based cross-sectional survey study was conducted during the period of August to December 2016 on some villagers of Tangail area in Bangladesh using a pre-standardized questionnaires called "IUATLD -1984 bronchial symptoms questionnaires", designed by the International Union Against Tuberculosis and Lung Diseases (IUATLD). The demographic data of the study subjects were collected by interviewing the subjects and the data were analyzed using SPSS software. Results: The results demonstrated that a substantial proportion of study subjects showed the main characteristic symptoms of asthma i.e., wheeze last 12 months is about 18.27%, shortness of breath (SOB) without strenuous work were 21.84%, nocturnal SOB 14.70%, morning cough 13.26%, nocturnal cough 17.25% and morning phlegm 10.37%. Overall 9.69% of the subjects were found to be asthmatic. Female study subjects showed more asthmatic complications than male subjects and in the higher aged group asthmatic symptoms were more prevalent. Conclusions: Among the study subjects, asthmatic complications were found to be substantial. Further clinical study is necessary to confirm the findings.